FICTIONAL GAY CHARACTERS AS SEEN IN US TV SERIES ‘ARROW’ SEASON 1 – SEASON 8 (EUFONI: Journal of Language, Literary, and Cultural Studies, 2022)
The existence of LGBT characters in US TV Series had developed massively these days. This research focused on fictional gay characters in US TV Series entitled ‘Arrow’ from Season 1 until Season 8 – Finale, which is from 2012 until the early 2020. The theory of gender and sex, LGBTQ and TV representation, as well as heteronormativity have been used to analyze gay characters through their role, their emotions, and their conversation in the movie. Qualitative method with content analysis has been used to describe about all the findings. This qualitative content analysis is used as an analytical tool to explore the characteristics and the texts as the visual elements of the scene dialogues. The result showed that there are characteristics of LGBTQ characters: gendered stereotype, victimization, villain, sexual/no sexual depiction, and equality rights. Gay characters in Arrow fulfill three out of five characteristics. Those characteristics including villain, no sexual depiction, and equality rights.